2018
DOI: 10.1016/j.livsci.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting phenotype diversity in a local animal genetic resource: Identification of a single nucleotide polymorphism associated with the tail shape phenotype in the autochthonous Casertana pig breed

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In this study, 68% of animals had a straight tail; this value is close to 72% were found by Subalini et al (2010) and in the same direction of prevalence (98.5%) reported by Ritchil et al (2014). The strait tail might represent a feature of unselected pigs or that also are adapted to extensive production systems where tail biting is not a problem, considering that pigs with strait tails might more frequently be affected by this problem that is quite frequent in intensive production systems where animals are raised inside, with high density (Bertolini et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, 68% of animals had a straight tail; this value is close to 72% were found by Subalini et al (2010) and in the same direction of prevalence (98.5%) reported by Ritchil et al (2014). The strait tail might represent a feature of unselected pigs or that also are adapted to extensive production systems where tail biting is not a problem, considering that pigs with strait tails might more frequently be affected by this problem that is quite frequent in intensive production systems where animals are raised inside, with high density (Bertolini et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The overall F ST value obtained in the present work (analyzing data of 70K SNP chip) is considerably lower than the one observed in our previous study (0.27) 8 performed with an array of selected SNPs. This difference is expected because in the latter study only 39 causal mutations and polymorphisms in candidate genes were used whereas, in the present work, SNP markers across the whole genome and mostly neutral were used 6 . In addition to this, the distribution of different genetic diversity parameters estimated for each SNP marker is shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Despite a few whole genome studies have been carried out for some European local pig breeds, such as the Iberian 4,5 or Casertana 6,7 , many other autochthonous breeds have not been analyzed in detail yet and are considered untapped genetic resources. Recently, the diversity at several relevant candidate gene polymorphisms has been evaluated in twenty local European pig breeds 8 , providing information about the segregation of interesting markers for breeding or traceability 9,10 purposes and giving some first insights into the genetic structure of these populations.…”
Section: Introductionmentioning
confidence: 99%
“…These regions can provide insights into the biological mechanisms that explain domestication and lead to morphological differentiation, specialized production performances and, in some cases, disease resistance and resilience (e.g. [5][6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies are based on small numbers of animals and provide preliminary information on their population structure. In the case of the Iberian and Casertana breeds, quantitative trait loci (QTL) and genome scans have identified genomic regions and mutations associated with morphological, production, meat and carcass traits [9,10,16,17,[22][23][24]. Other studies have compared SNP datasets from Italian autochthonous and commercial breeds to identify population-informative markers and analyse their inbreeding levels [25,26].…”
Section: Introductionmentioning
confidence: 99%